Reconocimiento de espacios con optimización de trayectorias utilizando el robot “turtlebot3 burger” (2020)
This research is a contribution to mobile robotics for the planning of trajectories of an autonomous robot. For the case study, the TURTLEBOT3 BURGER robot will be used. With this device performance tests were carried out inside a hexagonal track. Each test has an increasing level of complexity, which allowed determining an algorithmic execution with results that lead to incremental development in robot programming. The results obtained are conditioned by the hardware and software connection and programming modes, through the use of the Robot Operating System (ROS), and the execution of a series of tests that focus on applying "Dijkstra and A Star" algorithms that allow optimizing routes with a robot and simulate them in "Rviz" as a 3D visualization tool for ROS applications. Finally, the theoretical part related to the work of algorithms and their programming was verified using this robotic platform, which manages to demonstrate that the initially proposed, defined objectives are met, such as the recognition and planning of a trajectory on flat terrain with obstacles , from a starting point to an end point as a target or arrival point.